Fabrikasi Papan Serat Tandan Kosong Kelapa Sawit dengan Penambahan Bahan Fluoresensi Fosfor - Husna, Ropiqotul; Yana, Debi; Kusmawati, Intan; Aisah, Nurul; Ginting, Delovita; Syahputra, Romi Fadli (JMPM (Jurnal Material dan Proses Manufaktur), 2023)
Natural fiber can be used as a substitute for environmentally friendly composite materials. Oil palm empty fruit bunches (OPEFB) is one of the natural fibers processed by the palm oil industry which is available in large quantities. The use of OPEFB fiber as an innovative fiberboard has not been studied much physically. The addition of fluorescence additives gives wood and fiberboard products the advantage of having a high aesthetic value. The aim of this study was to fabricate an innovative fiberboard biocomposite based on OPEFB fiber with the addition of phosphor fluorescence. Fiberboard is fabricated by hand lay-up and cold compaction methods. The main composition of the fiberboard consists of OPEFB fiber, epoxy resin, and 5 g of phosphorus powder. The fiber content of OPEFB varies from 76% to 86%. The results of physical testing showed that the fiberboard density ranged from 0.34 -0.59 g/cm³ and its water absorption capacity was 105.22 -156.475%. The specific heat capacity value of fiberboard ranges from 0.34 -2.2 J/g ̊C and its thermal conductivity is 0.001-0.002 W/mK. Meanwhile, the bending strength is 1.30 –6.42 MPa which is relatively comparable to bio-composite fiberboard. The addition of phosphorus affects the thermal properties of fiberboard, so it is suitable for application as a bio-insulator with fluorescence features.